Comparison of the Variability of Small Extracellular Vesicles Derived from Human Liver Cancer Tissues and Cultured from the Tissue Explants Based on a Simple Enrichment Method - Jie Chen; Zhigang Jiao; Jianwen Mo; Defa Huang; Zhengzhe Li; Wenjuan Zhang; Tong Yang; Minghong Zhao; Fangfang Xie; Die Hu; Xiaoxing Wang; Xiaomei Yi; et al. (Stem Cell Reviews and Reports, 2022)
A potential use of small extracellular vesicles (sEVs) for diagnostic and therapeutic purposes has recently generated a great interest. sEVs, when purified directly from various tissues with proper procedures, can reflect the physiological and pathological state of the organism. However, the quality of sEV is affected by many factors during isolation, including separation of sEV from cell and tissues debris, the use of enzymes for tissue digestion, and the storage state of tissues. In the present study, we established an assay for the isolation and purification of liver cancer tissues-derived sEVs (tdsEVs) and cultured explants-derived sEVs (cedsEVs) by comparing the quality of sEVs derived from different concentration of digestion enzyme and incubation time. The nano-flow cytometry (NanoFCM) showed that the isolated tdsEVs by our method are purer than those obtained from differential ultracentrifugation. Our study thus establishes a simple and effective approach for isolation of high-quality sEVs that can be used for analysis of their constituents. Graphical abstract

S-Adenosylmethionine-induced adipogenesis is accompanied by suppression of Wnt/β-catenin and Hedgehog signaling pathways - Yang Liu; Wentao Lv; Boyang Yu; Tingting Ju; Feiyun Yang; Meihua Jiang; Zuohua Liu; Ling Xu; Wenjuan Sun; Jinxiu Huang; Defa Li; Jingdong Yin (Molecular and Cellular Biochemistry, 2013)

Oct-1 functions as a transactivator in the hormonal induction of β-casein gene expression - Bing Dong; Chengfei Huang; Defa Li; Feng-Qi Zhao (Molecular and Cellular Biochemistry, 2009)